Use of LAMP Detection to Identify Potential Contamination Sources of Plant-Pathogenic Pythium Species in Hydroponic Culture Systems of Tomato and Eustoma - Feng, Wenzhuo; Nukaya, Akira; Satou, Mamoru; Fukuta, Naoko; Ishiguro, Yasushi; Suga, Haruhisa; Kageyama, Koji (Plant disease, 2018)
Hydroponic culture systems are subject to high risks of diseases caused by zoosporic plant pathogens. Control is generally difficult because of the rapid spread of zoospores in the nutrient solutions. In Japan, tomato and eustoma, which are cultivated using the D-tray and nutrient film techniques, respectively, are susceptible to diseases caused by Pythium aphanidermatum and P. irregulare. We used loop-mediated isothermal amplification to identify potential contamination sources of these two pathogens by monitoring their presence in the water supply wells, seedling terraces, nutrient solutions, diseased plants, and ground soils of a tomato greenhouse complex and a eustoma greenhouse complex. The results indicated that the pathogens may enter the culture systems from the soils around the greenhouses. Entry most likely occurs when seedlings are moved from the seedling terraces to the greenhouses, and sterilization of the hydroponic systems may not be sufficient. Therefore, monitoring pathogens in the culture systems and ground soils is very important for the management and prevention of these diseases.